MY CART (5)

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price:

There are no items in this cart.
Continue Shopping
                   


 Integration from 0 to infinity x2 / (xsinx ecosx)2


3 years ago

Share

Answers : (1)

                                        integral lim x=0 to infinity x^2/x^2sin^2xe^2cos^2x
=integral lim x=0 to infinity 1/sin^2xe^2cos^2x
=1/e^2integral lim x=0 to infinity4/(2sinxcosx)^2
=4/e^2integral lim x=0 to infinity dx/sin^2(2x)
=4/e^2 integral lim x=0 to infinity cosec^2(2x) dx
=4/e^2 [(-cot2x)/2] x=0 to infinity
=2/e^2[-cot infinity+ cot0]
=infinite
Thanks & Regards
Rinkoo Gupta
AskIItians Faculty
one year ago

Post Your Answer

More Questions On Integral Calculus

Ask Experts

Have any Question? Ask Experts

Post Question

 
 
Answer ‘n’ Earn
Attractive Gift
Vouchers
To Win!!!
Click Here for details
hey image attached please tell the method which is used in solution …..please sir .maam …..please anyone …...
 
 
Ans: Hello student, Please find the answer to your question below [t] = 0, 0 <=t < 1 [t] = 1, 1 <= t < 2 Now looking at the problem in hand There are total 100 term in L out of...
  img
Jitender Singh 7 months ago
 
sir is it greatest integer fn is used
 
milind 7 months ago
in numerator first term is e raise to power integral part of x ….....please explain anyone please ...please...
 
 
Hi, Convert the expression into e^2x ( by eliminating the e^-x term) Now analyse. The denominator is always positive. Demoninator > Numberator always. Ie. values are less than 1. So not...
  img
Yash Baheti 7 months ago
Calcilate the area bounded between the curves y = x and y = lnx from 0 and 1.
 
 
Ans: Hello Student, Please find answer to your question below y = x y = lnx Area b/w curves ‘A’
  img
Jitender Singh 8 months ago
 
first we should find the area covered by the line in the interval oto1 then we find area covered by the curve lnx in the interval 0 to 1 then the difference gives us the answer
 
pavansai 7 months ago
what is (x+3)(x -2)??
 
 
Hello Student, Please find the answer to your question (x + 3)(x – 2) = x^2+x-6 Hope that you will be satisfied with this
  img
Pankaj 9 months ago
 
absolutely correct. x(x – 2) + 3(x – 2) = x^2 – 2x + 3x – 6 = X^2 + x – 6 Hope that you both have understood now
  img
Pankaj 9 months ago
 
(x + 3)(x – 2) =x(x – 2) + 3(x – 2) = x^2 – 2x + 3x – 6 = X^2 + x – 6 Hope that you will understand now
  img
Pankaj 9 months ago
Find the equation of the straight line which is tangent at one point and normal at another point on the curve x=3t^2 , y=2t^3
 
 
The slope of the tangent at P(t) is dy/dx = dy/dt * dt/dx = t Let the tangent cuts the curve and normal at Q(t 1), then the coordinates of the point is (3t 1 2 , 2t 1 3 ) The the slope of...
 
Y RAJYALAKSHMI 8 months ago
Please prove …..and also give explanation sir please
 
 
Ans: Thanks & Regards Jitender Singh IIT Delhi askIITians Faculty
  img
Jitender Singh 9 months ago
 
Sir but what is answer
 
milind 9 months ago
View all Questions »